NATIONAL-CULTURAL AND UNIVERSAL FEATURES OF PROVERBS IN ENGLISH AND UZBEK - Boqiyeva Marjona Shuhratovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article examines the role of “proverbs” in English and Uzbek cultures. In this article several ideas about proverbs and their peculiarities have been done by famous writes and researchers. This article will be useful in my own research as I develop a clear theoretical framework for the role of proverbs in in English and Uzbek cultures.